Evolutionary retrospective of the formation and development of modern law (Discourse of Law and Administration, 2023)
The article is aimed to attract the attention of not only theorists, but also historians of the study of law to the fact that the latter began its evolution from “custom”. It is the latter that is based on worldview recognition and submission. It was closer to justice, and therefore met the ideas of the ideal of the law as the supreme good; it provides peace, order and mutual understanding. According to the authors, the current legislation, as well as the formation of the state, has passed a significant historical path of its formation and development from the primitive custom to the positive law sanctioned by the state. Moreover, in the early states, custom prevailed even with persistent and constantly strengthened attempts by public authorities to influence the legal status of society and dominate it through the judicial and administrative apparatus. This, in turn, ensured a gradual combination of various forms of legal regulation originating from society and the state. The very origins and foundations of the current legislation can be found even in the social regulation of primitive society, which was carried out with the help of customs, taboos, morality, and the like. Moreover, the basic principles of customary law as the first form of positive law were mythological and religious principles, which were also developed and supplemented in the further development of its forms. The sources of the current legislation which reflect the historical beginning of its gradual formation and development are different in certain spatial and social dimensions.
Keywords: law evolution; theory of law development; current legislation; state; custom; current law; positive law